Sadness Metaphors and Metonymies in Turkish Body Part Idioms - Melike Baş; Nalan Büyükkantarcıoğlu (Dilbilim Araştırmaları Dergisi)
This study examines the conceptualizations of the negative emotion sadness in Turkish body part idioms. More specifically, it addresses two main problems: (i) distribution of the body part terms used in idioms to express sadness, and (ii) conceptual metaphors and metonymies underlying the body part idioms that express sadness. The data of the study includes the idioms, which contain body part terminologies and communicate sadness. Conceptual metaphors and metonymies were identified following Barcelona (1997) and Kövecses (2000). The findings reveal that the body parts heart (yürek, kalp) and liver/lung (ciğer) are more productive in Turkish for the conceptualization of sadness. Among the conceptual mappings identified, physical damage is the most typical one with the highest number of linguistic items. Turkish data provide insights on the cultural-cognitive model of sadness, as well as on the embodied nature of emotions.